Inactivation Efficiency of Bacillus atrophaeus Spores on Seeds of Barley, Wheat, Lupine and Rapeseed by Direct Cold Atmospheric Pressure Plasma - Nicola Wannicke; Jasmin Martins Dias; Thalita M. C. Nishime; Henrike Brust (Applied Sciences)
The objective of this study was to evaluate the antimicrobial effect of direct cold atmospheric plasma (CAPP) treatment for pre-harvest application using four different crop species: Hordeum vulgare L. (barley), Triticum aestivum L. (wheat), Brassica napus L. (rapeseed) and Lupinus angustifolius L. (lupine). The model bacterium Bacillus atrophaeus served as a proxy for spore-forming plant pathogens on the seed surface. After semi-dry inoculation of spores onto the seeds, treatment with two different plasma sources, a volume-dielectric barrier discharge and a corona discharge, and different exposure times was carried out. Subsequently, recovery of viable spores from the seeds’ surfaces was performed. Moreover, seed viability was determined based on maximum germination, as well as water contact angle as a measure for seed surface hydrophilicity. Direct CAPP treatment was efficient in reducing viable spores of B. atrophaeus with no significant differences between the plasma sources, reaching a mean inactivation of 1 log10 CFU/mL across all treatment times and crops species. Maximum germination of seeds was not negatively affected under any treatment condition. Seed hydrophilicity was increased for both plasma sources tested. Overall, this study provides valuable information on the efficiency of direct CAPP treatment of seeds with the purpose of seed hygienization with the premise of unaltered seed vitality and evaluates the potential application in comparison with previous investigated CAPP methods.